Insights in the Thermal Volume Transition of Poly(2‐oxazoline) Hydrogels. Issue 18 (25th June 2021) - Segiet, Dominik; Stockmann, Annika; Sadowski, Jan; Katzenberg, Frank; Tiller, Joerg C.
Abstract: Polymers with a lower or an upper critical solution temperature (LCST or UCST) can precipitate in a very narrow temperature range. Cross‐linking of such polymers and adding them to suited solvent results in smart gels that are capable of greatly changing their dimensions with changing temperature. This transition occurs very often in a broad temperature range, which limits the applicability of smart materials. To shed some light into the design of thermo‐responsive hydrogels with a narrow phase transition, poly(2‐ethyl‐2‐oxazoline) (PEtOx), poly(2‐isopropyl‐2‐oxazoline), and statistical copolymers of 2‐butyl‐2‐oxazoline and 2‐ethyl‐2‐oxazoline, respectively, are synthesized and the concentration‐dependent cloud point temperatures ( T cp ) of the free polymers in aqueous media are determined in relation to the thermo‐responsive swelling behavior of the respective hydrogels. A narrow thermal transition of the hydrogels can only be achieved when the T cp of the free polymers in water is independent on the concentration. Aqueous salt solutions can render even PEtOx into a concentration independent LCST polymer. However, this salt effect does not work for hydrogels. Abstract : To shed some light into the design of thermo‐responsive hydrogels with a narrow phase transition, different poly(2‐oxazolines) exhibiting a lower critical solution temperature are cross‐linked and the concentration‐dependent cloud point curves in aqueous media and the thermo‐responsive swelling behavior of the respective hydrogels are determined. A narrow volume transition is only found, if the respective free polymer exhibits a concentration‐independent cloud point curve.